Isolation and Identification of Plant Growth Promoting Rhizobacteria from Sago Palm (Metroxylon sagu, Rottb.) - Samuel Lihan,; Flonia Benet,; Awang Ahmad Sallehin Awang Husaini,; Kasing Apun,; Hairul Azman Roslan,; Habsah Hassan, (Tropical Life Sciences Research, 2021)
Plant growth promoting rhizobacteria (PGPR) are strains of naturally occurring soil bacteria that live in close vicinity to the plant’s rhizosphere region which possess the capability to augment host growth. This study was conducted to isolate and identify potential PGPR isolates indigenous to Metroxylon sagu, Rottb. rhizosphere. These potential isolates were characterised based on their beneficial plant growth promoting (PGP) properties and identified by molecular analysis via 16S rDNA sequencing. A total of 18 isolates were successfully isolated, out of which five isolates were tested, and designated as (S1A, S2B, S3A, S3C and S42). Among the five isolates, two isolates (S2B and S3C) were found to produce high levels of indole-3-acetic acid (2.96 ?g/mL and 10.31 ?g/mL), able to fix nitrogen and show significant activity in phosphate solubilisation. The analysis of their sequences via National Center for Biotechnology Information (NCBI) suggested their close identity towards Lysinibacillus sphaericus and Bacillus thuringiensis. It can be concluded that the isolated PGPR possesses beneficial PGP attributes. It can be implied that the isolated PGPR are potential to be used as inoculant biofertilisers, beneficial for Metroxylon sagu, Rottb. growth. Hence, further studies need to be done to evaluate the effectiveness of the beneficial microbes towards sago seedlings growth, under pot experiment.